Pemberdayaan Perempuan melalui Pelatihan Membatik di Kelurahan Lengkong Gudang Kota Tangerang Selatan - Agam Akbar Pahala; Fariz Al Hazmi; R.A Ataswarin Oetopo (Institut Seni Indonesia Surakarta, 2025)
Enhancing creativity and skills is a crucial aspect of economic and welfare improvement initiatives. Batik, as a work of art with high value, has its own market that is in great demand by the community. Currently, Lengkong Gudang Village, South Tangerang City does not have a superior craft product that is competitive. The purpose of this batik training is to target participants from the Family Welfare Development women's group in Lengkong Gudang Village, providing them with batik skills. The activities are carried out in stages, starting with preparation, which includes creating teaching materials in the form of handouts and preparing tools and materials. This is followed by core activities, such as batik making training using cotton fabric, and the final stage of evaluation through discussion. The training method is a demonstration method that is more focused on the process of making the work. The results of this training, the participants were able to produce batik works with stamping and writing techniques. Although there were several obstacles, the participants seemed enthusiastic about completing the entire series of activities. The demonstration method also makes it easier for participants to understand the steps in batik because the instructor provides explanations and practices the method. Keywords: Training, Batik Making, Family Welfare Development, Women Empowerment, Fine Arts